THE STUDENTS DIFFICULTIES IN UNDERSTANDING ANAPHORA AND CATAPHORA ON NEWS ITEM TEXT AT SEVENTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF BATURAJA UNIVERSITY - Shofiyatul Huriyah (Concept : Community Concern for English Pedagogy and Teaching, 2017)
The objectives of this study were to find out the students’ difficulties in understanding anaphora and cataphora and to find out the factors that influence students’ difficulties in understanding anaphora and cataphora on news items text. Technique for collecting the data was test and questionnaire. The method of this study was descriptive method. The writer took all of seventh semester students as a sample, and the total number of sample was 46 students. Based on the result of the data analysis, it was found that the students’ difficulties in understanding anaphora in divorcement was 18% and ambiguity was 82 %. The students difficulties in understanding cataphora in divorcemet was 25%, ambiguity was 44%, and Common searching backward than searching forward 31%. The writer also found that the most difficult problem that faced by the students was understanding cataphora, it refers to 58% of difficulties while anaphora 42%. The result of the questionnaire show that, there were two factors that most influences students in learning anaphora and catphora. They were 1) lecturers’ knowledge, enthusiasm and responsibility for learning and 2) effective interaction between the lecturer and the students. Key words: Difficulties, Anaphora, Cataphora, News, Items, Text